Physical characteristic analysis of solenoid-based coil structure - Sulaiman, Nadzril; Yunas, Jumril; Sugandi, Gandi; Yeop Majlis, Burhanuddin (Trans Tech Publications, Switzerland, 2012)
Measurement of low magnetic field has played an important role in many electronics applications such as military, non-destructive test, medical diagnosis and treatment. The presence of magnetic field, particularly the strength and direction, can be measured using magnetometer. Fluxgate magnetometer is one of the prominent type among many types of magnetometer due to its simple operating principle, robustness and durability. The main components of fluxgate magnetometer consisting of Driving Coils, Sensing Coils and Magnetic Core. In recent years, fluxgates are increasingly made into micro-scale through MEMS silicon processing technology. Physical characteristics of fluxgate coils such as width of the coil; distance between successive coil; and gap between top and bottom coils have an effect towards device miniaturization and performance. Therefore, physical characteristic analysis of coils is significant. This paper highlights analysis on physical characteristics of solenoid-based coil structure for a micro-scaled fluxgate magnetometer by means of finite element method (FEM) simulations. The results of this analysis can be used to design proper coils that could improve the performance of the device.